Methods of Using Twitter in Marketing the Activities of Public Relations Departments in the Saudi Airline Market - Aljabri, Khalid Hamed (Journal of Humanities & Social Sciences, 2022)
The study aimed to identify the most important marketing activities of public relations departments in the Saudi aviation market, and to identify the methods of using Twitter in the marketing activities of public relations departments in the Saudi aviation market. It also aimed to reveal its strengths and weaknesses, and to monitor the content of marketing tweets published by public relations departments in the Saudi aviation market via Twitter. The study sample consists of the twitter accounts of the General Authority of Civil Aviation, Saudi Arabian Airlines, and Flynas. The study concluded that the most important marketing activities of the public relations departments in Saudi Airlines and flynas were to respond to the customer in private, and then allocate a number for the customer to follow up with him. The study concluded by extracting the most prominent methods of using Twitter in the marketing activities of public relations departments in the Saudi aviation market, where these methods consisted of communicating with the customer with the reservation number for his service, then responding to the customer in private, and then welcoming the customer. The study also showed that the most important strengths in the marketing activities of public relations departments in the Saudi aviation market are the immediate response to the customer’s inquiry, and then allocating a number to follow up the customer’s complaint. On the other hand, the most important weaknesses in the marketing activities of the public relations departments in the Saudi aviation market are that communication takes place only via the ticket number or the reservation reference number, and then the weakness of scheduling new flights. The study showed that the most prominent contents of the marketing tweets published by the public relations departments in the Saudi aviation market consisted of re-tweets and admiration, and then directing customers to their inquiries.